Outcome of salvage surgery for anal squamous cell carcinoma. (29th August 2013) - Harris, D. A.; Williamson, J.; Davies, M.; Evans, M. D.; Drew, P.; Beynon, J.; ,
Abstract: Aim: The purpose of this study was to examine factors related to treatment failure following chemoradiotherapy for squamous cancer and to compare the outcome of salvage surgery in one unit with national audit standards published by the Association of Coloproctology of Great Britain and Ireland (ACPGBI) (ACPGBI position statement for management of anal cancer. Colorectal Disease 2011; 13(Suppl. 1): 1–52). Method: Patients with squamous cell carcinoma of the anus treated with radical intent between 1997 and 2010 in a single tertiary referral oncology institute were prospectively identified. Multivariate analysis was used to establish factors associated with treatment failure. Cancer‐specific end‐points after salvage surgery were determined by Kaplan–Meier survival analysis. Results: Ninety‐five patients received chemoradiotherapy with radical intent with a 5‐year overall survival of 83% (all stages) at a median follow up of 35 months. Of these, 11 (12%) required salvage surgery, five of whom were Stage T4 at presentation. Six patients had failed to respond to chemoradiotherapy and five presented with recurrence at a median of 10 (10–36) months. Only Stage T4 disease at presentation was predictive of the need for salvage surgery (OR 5.6, CI 4.9–6.3, P  = 0.015). There was no surgical mortality and no delayed perineal healing where a myocutaneous flap was used. The resection margin was involved in one (9%) patient. The 5‐year survival rate was 64%. Audit standards for case selection, local control, survival and perineal complications were achieved. Conclusion: Long‐term survival was achieved in two‐ thirds of patients following salvage surgery after failed primary chemoradiotherapy for anal cancer in a multidisciplinary oncological unit. Stage T4 disease at presentation strongly predicted the need for subsequent salvage intervention.